CAN METAMORPHIC REACTIONS PROCEED FASTER THAN BULK STRAIN? - Baxter E.F.; DePaolo D.J. (My University, 2004)
Available constraints on metamorphic reaction rates derived from the study of natural systems are similar to, or slightly lower than, the bulk strain rates measured in the same rocks. Here, we explore whether this apparent relationship is merely coincidence or due to a more fundamental mechanistic link between reaction and strain. Grain boundary migration accommodated dislocation creep (GBMDC) or grain boundary diffusion creep (GBDC) (i.e. pressure solution), both of which involve dissolution-precipitation as we define it, will occur simultaneously with mineral reactions involving dissolution-precipitation in the presence of a non-zero deviatoric stress. The exact relationships between reaction and strain are different depending on whether GBMDC or GBDC is controlling strain, but the mechanistic link exists in both cases. We present theoretical arguments which show that bulk strain by GBMDC or GBDC, which may additionally be accommodated by processes not involving dissolution-precipitation, such as dislocation glide and climb or grain boundary sliding, should in most cases be somewhat faster than the bulk reaction rates as observed. With few exceptions, for natural metamorphic systems undergoing plastic deformation, strain rates provide an upper limit for bulk reaction rates occurring simultaneously in the same rocks. The data suggest that mineral reaction rates may typically be within one order of magnitude of the strain rate.